2005
DOI: 10.1111/j.0014-3820.2005.tb00955.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic and Environmental Components of Morphological Variation: Skull, Mandible, and Molar Shape in Marmots (Marmota, Rodentia)

Radhekshmi Caumul,
P. David Polly

Abstract: Abstract. The phenotype is a product of its phylogenetic history and its recent adaptation to local environments, but the relative importance of the two factors is controversial. We assessed the effects of diet, habitat, elevation, temperature, precipitation, body size, and mtDNA genetic divergence on shape variation in skulls, mandibles, and molars, structures that differ in their genetic and functional control. We asked whether these structures have adapted to environment to the same extent and whether they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
203
1
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 229 publications
(224 citation statements)
references
References 76 publications
17
203
1
3
Order By: Relevance
“…A study on the outline of the first molar of extinct murine rodents demonstrated that different diet groups could be distinguished through geometric morphometric analysis (Cano et al 2013). However, in marmots and some Didelphidae it has been demonstrated that diet is weakly correlated with molar shape (Caumul andPolly 2005, Chemisquy et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study on the outline of the first molar of extinct murine rodents demonstrated that different diet groups could be distinguished through geometric morphometric analysis (Cano et al 2013). However, in marmots and some Didelphidae it has been demonstrated that diet is weakly correlated with molar shape (Caumul andPolly 2005, Chemisquy et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Limitations in analyses owing to insufficient sample size are common, particularly in paleontological samples (Matthews and Stynder 2011), as it was in ours. Is important to point out that geometric morphometrics and features from the molars can be used in other types of studies beyond taxonomic identifications, as for example: correlating changes in molar shape with paleoclimate aspects (McGuire 2010), phylogenetic (Caumul and Polly 2005), morphological evolution and environmental variations (Renaud and Van Dam 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Bookstein 1991;Rohlf & Marcus 1993;Adams & Rohlf 2000), this approach was followed in this study. As the skull phenotype is genetically and functionally more complex than teeth (Caumul and Polly 2005;CordeiroEstrela et al 2008), it probably represents relevant biological variation of underlying natural groups. Table 1).…”
Section: Morphological and Geoclimatic Data Acquisitionmentioning
confidence: 99%
“…Inter-group skull and bulla size differences between all the M. crassus groups, as defined for the shape analysis at an intra-specific level, and M. libycus were tested by a Kruskal-Wallis test (with Bonferroni correction) using PAST. As the ventral cranium contains a larger number of evolutionarily independent components of variation (Caumul & Polly 2005) as well as the main part of the tympanic bulla, only the size differences obtained from the ventral view are plotted in Fig. 5.…”
Section: Size Analysismentioning
confidence: 99%
See 1 more Smart Citation